Analysis of publications on the topic of Energy with a STS focus on Science Teaching in Brazil between 2006 and 2017 (Research, Society and Development, 2021)
The purpose of this article is to present and analyze the research that investigate the theme Energy addressed under the assumptions of the CTS (Science, Technology and Society) movement in Brazil between 2006 and 2017. Thirty papers published in periodicals and annals of events were identified, whose analysis allowed to identify some aspects categorized in general characteristics, nature of the work and thematic focus. It was found that the High School is the level of schooling that presents the highest concentration of production analyzed and that there are few jobs directed to Elementary School and teacher training. Most of the works investigated comprise a range of didactic-pedagogical activities, using didactic sequences, where the theme Energy was supported in the CTS approach. This study is expected to better understand the research carried out in the field of Science Education related to the topic Energy developed under the CTS approach, providing descriptions and analyzes that allow a better understanding of the training and development of this area of research.